2021
DOI: 10.1002/aur.2523
|View full text |Cite
|
Sign up to set email alerts
|

Decreased homotopic interhemispheric functional connectivity in children with autism spectrum disorder

Abstract: While several functional and structural changes occur in large‐scale brain networks in autism spectrum disorder (ASD), reduced interhemispheric resting‐state functional connectivity (rsFC) between homotopic regions may be of particular importance as a biomarker. ASD is an early‐onset developmental disorder and neural alterations are often age‐dependent. Although there is some evidence for homotopic interhemispheric rsFC alterations in language processing regions in ASD children, wider analyses using large data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In a study that only used data from children with ASD (5–10 years old) from both ABIDE I and II, and further controlled for center/scanner variability, a similar pattern of decreased homotopic rsFC was found to that reported by Li et al . ( 2019 ) across different ages in ABIDE I, but positive correlations between strengths of homotopic rsFC in regions of the DMN and visual cortex and ASD symptom severity (Yao et al ., 2021b ). The positive correlation with symptoms in children may reflect abnormal developmental trajectories of homotopic interhemispheric rsFC in ASD (Kozhemiako et al ., 2019 ; Ma et al ., 2022 ).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that only used data from children with ASD (5–10 years old) from both ABIDE I and II, and further controlled for center/scanner variability, a similar pattern of decreased homotopic rsFC was found to that reported by Li et al . ( 2019 ) across different ages in ABIDE I, but positive correlations between strengths of homotopic rsFC in regions of the DMN and visual cortex and ASD symptom severity (Yao et al ., 2021b ). The positive correlation with symptoms in children may reflect abnormal developmental trajectories of homotopic interhemispheric rsFC in ASD (Kozhemiako et al ., 2019 ; Ma et al ., 2022 ).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Of these VMHC studies, only one has reported associations between homotopic rsFC and CC structure, with a trend for caudate rsFC being negatively correlated with volume of the anterior CC (Yao et al ., 2021b ). Previous studies have consistently revealed reduced CC volume in ASD, although specific subregions vary across studies due to differences in sample size, analysis approaches, and age of participants (see Yao et al ., 2021a ).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…https://mc03.manuscriptcentral.com/sab | Stress and Brain 9 disorders. For example, clinical studies have revealed that homotopic interhemispheric connectivity is significantly reduced in children, adolescents, and adults with an autism spectrum disorder [23,24]. In addition, a recent study showed that unilateral BLA PNs send dense projection to contralateral BLA via the posterior part of the anterior commissure [12].…”
Section: Stress and Brainmentioning
confidence: 99%
“…Specifically, structural deficits of the CC have been found in patients with autism spectrum disorder (ASD) [9][10][11][12] and epilepsy [13][14][15] and associated mice models [16][17][18][19]. A growing body of work supports that FC is also disrupted in NDD [13,[20][21][22][23], in fact two studies examining large cohorts of children with ASD (ABIDE I and II) report abnormalities of interhemispheric FC [21], and found evidence of hyperconnectivity in the anterior cingulate/medial prefrontal cortex (ACC/mPFC) [24]. Most importantly, the degree of disrupted interhemispheric connectivity correlates with ASD severity [20,22,24,25].…”
Section: Introductionmentioning
confidence: 99%